A comparison study on hydrocarbon composition in bitumens I and II from Lower Cambrian marine shales in Guizhou Province, South China. (1st May 2019) - Li, Yan; Xia, Jia; Song, Zhiguang
Highlights: Hydrocarbons in bitumens I and II from highly mature sediments were compared. The relative abundance of biomarkers are obviously different in bitumen fractions. High abundance of tricyclic terpanes and diginanes were detected in bitumen II. Bitumen II may provide more reliable information on source input and maturity. Abstract: The composition and distribution of hydrocarbons in the initial solvent extracts (bitumen I) and corresponding secondary extracts (bitumen II) of kerogens in the Lower Cambrian marine shales from Guizhou Province of South China, were comparatively studied. The goal of this study is to explore whether the secondary extracts can provide the compensatory information on the source inputs of original organic matters, depositional environments and thermal maturity in highly mature shales. The results show that their similarities are mainly reflected by the same components of hydrocarbons, such as n -alkanes, acyclic isoprenoids, terpanes, and steranes detected in two bitumen fractions. These similarities suggest that the hydrocarbons in bitumens I and II are generally indigenous. Whereas the relative abundances of tricyclic terpanes (TT) and diginanes are significantly high in bitumen II, as their ratios of C21 TT/αβC30 hopane and C21 /20R αααC27 sterane in bitumen II are much higher than those in bitumen I. Bitumen II is also characterized by a relatively higher abundance of low carbon number alkanes as the C21 −/C22+ ratios in the range of 8.4–31.5 contrasted to 0.9–5.2 in bitumen I. The hydrocarbons and their related ratios indicate that bitumen II had reserved some intact features of the initial hydrocarbon composition, and therefore may provide useful information on the source input and thermal maturity of organic matters in the highly mature sediments, whose initial soluble organic matters were heavily degraded and/or overprinted.